2021
DOI: 10.1377/hlthaff.2020.01990
|View full text |Cite
|
Sign up to set email alerts
|

Unmet Social Needs And Worse Mental Health After Expiration Of COVID-19 Federal Pandemic Unemployment Compensation

Abstract: Federal Pandemic Unemployment Compensation (FPUC) provided unemployment insurance beneficiaries an extra $600 a week during the unprecedented economic downturn during the coronavirus disease 2019 (COVID-19) pandemic, but it initially expired in July 2020. We applied difference-in-differences models to nationally representative data from the Census Bureau's Household Pulse Survey to examine changes in unmet health-related social needs and mental health among unemployment insurance beneficiaries before and after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 26 publications
4
37
0
Order By: Relevance
“…These findings strongly suggest a need for increased support for school food programs, enabling these important programs to ensure that meals reach families in need. Similarly, NFACT sites universally found a higher prevalence of food insecurity among households that experienced job or income loss during the pandemic compared to households with no change in employment status, a finding aligned with other recent research ( 15 , 25 , 56 ).…”
Section: Discussionsupporting
confidence: 83%
“…These findings strongly suggest a need for increased support for school food programs, enabling these important programs to ensure that meals reach families in need. Similarly, NFACT sites universally found a higher prevalence of food insecurity among households that experienced job or income loss during the pandemic compared to households with no change in employment status, a finding aligned with other recent research ( 15 , 25 , 56 ).…”
Section: Discussionsupporting
confidence: 83%
“…These findings strongly suggest a need for increased support for school food programs, enabling these important programs to ensure that meals reach families in need. Similarly, NFACT sites universally found higher prevalence of food insecurity among households that experienced job or income loss during the pandemic compared to households with no change in employment status, a finding aligned with other recent research (15,24,42).…”
Section: Discussionsupporting
confidence: 84%
“…In the U.S., unemployed men and women receiving means-tested or welfare benefits were found to be more likely to report depression, in both the short and long term [ 70 ]. In another U.S. study, depression and anxiety symptoms increased among households who reported receiving unemployment insurance benefits, relative to a period when an unemployment insurance benefit was in effect [ 71 ]. Therefore, the direction of the association for this finding may not necessarily mean that receiving the COVID-19 relief materials induced moderate/severe psychological distress among recipients, but rather that recipients may have already been moderately/severely psychologically distressed (reverse causation) due to their difficult financial or social conditions.…”
Section: Discussionmentioning
confidence: 99%